2020
DOI: 10.7759/cureus.9649
|View full text |Cite
|
Sign up to set email alerts
|

Central Nervous System Miliary Brain Metastasis Secondary to Breast Cancer: Case Report

Abstract: Miliary metastasis to the central nervous system (CNS) is a rare presentation of metastasis mainly found in primary adenocarcinoma of the lung. Its association with breast cancer is even less frequent. We present the case of a 50-year-old female patient diagnosed in 2010 with stage IIA infiltrating ductal breast cancer RE (-), RP (+), HER 2 (-), HER2 NEU (+). She was treated with modified radical left breast mastectomy, radiation therapy, and chemotherapy. Her condition began presenting oppressive frontal head… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…In a recent review, only 26 cases of miliary CNS metastases have been reported and none of these cases were related to melanoma; the most frequent primary tumor was lung (61.54%), followed by breast and unknown origin, with 11.54% each [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent review, only 26 cases of miliary CNS metastases have been reported and none of these cases were related to melanoma; the most frequent primary tumor was lung (61.54%), followed by breast and unknown origin, with 11.54% each [8].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of CE is not fully known [8], but probably the BRAF V600E mutated could play a role in the onset of CE related to melanoma [5]; other research is needed to assess the possible role of this gene in the CE pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation